Discourse Ability in Speech Texts of Students of the Faculty of Letters, Nahdlatul Wathan University. - Zainul, Zainul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze students' ability to construct a complete speech based on structural elements such as a title, greeting, introduction, body, and closing. The method used is descriptive qualitative, analyzing speech texts from a number of students. The results indicate that although students understand these elements, their application is still limited and does not support speech cohesiveness. The use of greetings and other pragmatic expressions is often inconsistent, resulting in less effective messages. In addition, students experience difficulty in organizing data and facts comprehensively, and introductions and closings are often inadequate. These findings highlight the need for training and a deeper understanding of speech structure and discourse analysis to improve students' ability to construct cohesive, contextual, and meaningful speeches.